Re-evaluation of characters in Apolemiidae (Siphonophora), with description of two new species from Monterey Bay, California - Siebert, S.; Pugh, P.R.; Haddock, S.H.D.; Dunn, C.W. (Zootaxa, 2013)
Siphonophores are polymorphic planktonic marine Cnidarians. The family Apolemiidae is sister to all other species of physonect and calycophoran siphonophores. Although this enigmatic group arguably includes the longest animal species on the planet, their colony-level organization and growth patterns are not well understood. Here we describe two new apolemiid species: Apolemia lanosa sp. nov. and A. rubriversa sp. nov. We provide detailed descriptions of zooid budding and the organization of mature zooids within the siphosome. Our findings reveal that at least two distinct general patterns of siphosomal organization are found in different Apolemia species. In the first pattern, dispersed organization, zooids independently attach directly to the siphosomal stem. In the second pattern, pedunculate organization, only the gastrozooid is attached directly to the stem, and the other zooids of the cormidium branch from its peduncle. This diversity within Apolemia indicates that fundamental aspects of zooid budding and organization are homoplastic within Siphonophora, as both patterns are also found in other siphonophores. The observations presented here greatly clarify the interpretation of diagnostic characters within Apolemiidae, bear on the status of the three previously described species, provide critical detail for understanding the diversity of colony-level organization in siphonophores, and establish a foundation for the description of additional apolemiid species.